ANALISIS YURIDIS TERHADAP PENGANGKATAN PIMPINAN PERUSAHAAN DAERAH DIHUBUNGKAN DENGAN PEYELENGGARAAN PEMERINTAH YANG BAIK (GOOD GOVERNANCE) - RABUANDI, SE A.2021141018, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
AbstractThis thesis addresses the issue of juridical analysis of the Regional Corporate Leadership Appointment linked to the Implementation of the Government's Good (Good Governance). Of Results Using Normative Legal Research Methods conclusion In this study it can be concluded that the removal of the leadership of a local company (PDAM) Mempawah district does not comply with the legislation with the issuance of Decree of the Regent. A decree is contrary to the mandate of legislation governing the management of regional companies, should have been in terms of the formation, merger and changes in local companies must have a legal basis.